1983
DOI: 10.1007/bf00542222
|View full text |Cite
|
Sign up to set email alerts
|

Systemic availability of acetylsalicylic acid in normal men and women and its effect on in vitro platelet aggregability

Abstract: The systemic availability of acetylsalicylic acid (ASA) after oral ingestion of 1 g in an effervescent formulation was 16.3 +/- 2.0% and 16.9 +/- 3.2% of the ingested dose in normal women and men, respectively. The average plasma half-life of ASA in each sex was also identical at 18.5 +/- 1.4 and 18.1 +/- 1.2 min, respectively. The inhibitory effect of ASA on collagen-induced platelet aggregation in vitro on blood from both sexes was studied. The IC50 was 23.9 +/- 2.9 micrograms/ml in females and 22.5 +/- 2.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…These data are suggestive of intrinsically lower aspirin esterase metabolic activity in females, although it is acknowledged that the regulation of aspirin esterases in plasma may be different to that for the esterase(s) present in other tissues. Similar sex-related differences in aspirin AUC have also been reported by Ho et al (1985), but other studies have found no difference in aspirin AUC between males and females (Husted et al, 1983) or a larger aspirin AUC in males compared to females (Buchanan et al, 1983). In the present study more plasma samples were collected in the 2 h following aspirin administration than in the previous studies and this should provide a more accurate estimate of aspirin AUC and half-life.…”
Section: Discussionsupporting
confidence: 84%
“…These data are suggestive of intrinsically lower aspirin esterase metabolic activity in females, although it is acknowledged that the regulation of aspirin esterases in plasma may be different to that for the esterase(s) present in other tissues. Similar sex-related differences in aspirin AUC have also been reported by Ho et al (1985), but other studies have found no difference in aspirin AUC between males and females (Husted et al, 1983) or a larger aspirin AUC in males compared to females (Buchanan et al, 1983). In the present study more plasma samples were collected in the 2 h following aspirin administration than in the previous studies and this should provide a more accurate estimate of aspirin AUC and half-life.…”
Section: Discussionsupporting
confidence: 84%
“…Another factor in the lack of uniformity in research findings may lie in the dose of aspirin employed since Husted et al 11 could not find a sex difference when high in vivo doses (1 g/day) were used. We deliberately studied a high in vitro concentration of aspirin, however, to ensure complete inhibition of cyclooxygenase and to match that concentration used in our pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…Although measurement of the blood level of drugs such as aspirin is possible, it is not done routinely because of the rapid metabolism of these agents. 15 The pharmacological effects of ticlopidine result from the actions of its metabolite, but the blood level cannot be measured because this metabolite has still not been identified. 16 Accurate determination of thromboxane B 2 levels is possible, but this parameter cannot be used to distinguish the pharmacological actions of aspirin and ticlopidine because it only shows the total effect on platelet aggregation.…”
Section: Compliance With Antiplatelet Therapy In Patients With Ischemmentioning
confidence: 99%